THE CADOMIAN UNCONFORMITY IN THE SAXO-THURINGIAN ZONE, GERMANY: PALAEOGEOGRAPHIC AFFINITIES OF EDIACARAN (TERMINAL NEOPROTEROZOIC) AND CAMBRIAN STRATA - Buschmann B.; Elicki O.; Jonas P. (My University, 2006)
The most complete Ediacaran (terminal Neoproterozoic) to Early Cambrian record in the Saxo-Thuringian Zone is provided by the Cadomian-deformed Ediacaran Rothstein Formation and the unconformably overlying Early Cambrian Zwethau Formation in the Torgau-Doberlug Syncline (TDS). Conglomerates and greywackes of the marine Rothstein Formation are of continental magmatic arc provenance and record detrital zircon SHRIMP ages that indicate a Late Cryogenian to Early Ediacaran (700-580 Ma) age for the arc source and its emplacement into Palaeoproterozoic (2000 Ma) crust. Tuffaceous intercalations record extrabasinal eruptions of evolved calc-alkaline lavas that point to ongoing Cadomian continental arc magmatism. SHRIMP zircon ages from a tuffaceous layer date this volcanic activity and the formation's deposition as Late Ediacaran (566 ± 10 Ma). Close correlation in provenance and age to other Ediacaran units of the Saxo-Thuringian Zone points to a common palaeogeographic setting in the Avalonian-Cadomian belt. Detrital and inherited zircon ages, and Nd-isotopic ratios from these Ediacaran siliciclastic rocks suggest a position on the active margin of Gondwana near the West African craton. The Early Cambrian Zwethau Formation records the erosion of the underlying Ediacaran rocks followed by the successive evolution of: (i) a carbonate-dominated subtidal ramp with calcimicrobial-archaeocyathan buildups, (ii) a shallow-subtidal to intertidal mixed ramp with peritidal sediments, and oolite shoal complexes, and (iii) a more siliciclastic depositional environment. Calcimicrobial-archaeocyathan buildups, oolite shoals, and sulfate nodules in intertidal sediments indicate warm, arid to semi-arid climatic conditions and a palaeogeographic setting in equatorial to sub-equatorial latitudes. Archaeocyaths, the trilobite taxon Dolerolichia, and the sedimentary facies assemblages compare closely to those of the "Mediterranean" Early Cambrian, constraining the palaeogeographic setting to the European, sub-equatorial, western Gondwana shelf realm. Archaeocyaths record a mid-Early Cambrian (Middle Issendalenian/Ovetian) age, making these the oldest Cambrian sediments in both the Saxo-Thuringian Zone and the Bohemian Massif. The Middle Cambrian lithological and palaeontological records of the TDS closely resemble those of the Frankenwald area of the Saxo-Thuringian Zone as well as those of other fragments of the western Gondwana shelf in Spain, Morocco, and Bohemia. Archaeocyaths, Early Cambrian trilobites, and correlations with Morocco suggest Cambrian deposition commenced at ca. 520 Ma, such that the Cadomian unconformity represents a time gap of about 35-55 Ma (latest Ediacaran to Early Lower Cambrian). This gap, which is related to the Cadomian orogeny and so common to all areas of the Cadomian belt, obscures some of palaeobiological, palaeogeographic, and climatic change that marks the Precambrian-Cambrian transition. © 2006 Elsevier B.V. All rights reserved.
Keywords: CADOMIAN OROGENY; CAMBRIAN; EDIACARAN; NEOPROTEROZOIC; PALAEOGEOGRAPHY; SAXOTHURINGIAN ZONE; Paleozoic::Cambrian; Палеозой::Кембрийская; Precambrian::Proterozoic::Neoproterozoic::Ediacaran; Докембрий::Протерозой::Неопротерозойская::Эдиакарий